Expanding the taxonomic knowledge of Adelosgryllus Mesa & Zefa, 2004 (Orthoptera: Grylloidea: Phalangopsidae): description of four new species for Brazilian subterranean habitats - Merlo, Rayanne Lays Sant’ana; Castro-Souza, Rodrigo Antônio; Junta, Vitor Gabriel Pereira; Ferreira, Rodrigo Lopes (Zootaxa, 2022)
In this study, four new Brazilian species are described for the genus Adelosgryllus Mesa & Zefa, 2004, occurring in Minas Gerais, Tocantins and Pará states. Three of these species were found in caves and one was found in endogenous habitats, representing the first record of species form this genus for such habitats. The morphology of the phallic complex was used as the main criterion for distinguishing the new species, the copulatory papilla was also described for one of the new species. Finally, we bring a brief discussion about the ecology, distribution, and conservation of these species.